The Development Of Bilingual Information Boards To Support Recreational Tourism At Marisa Beach - Mendrofa, Cinta Tri Andalis; Harefa, Cinthika Joe Apriani; Gulo, Florencia Ananda; Harefa, Afore Tahir (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Recreational tourism destinations depend not only on natural attractions but also on the availability of supporting facilities that ensure effective information delivery, visitor safety, and comfort. One such facility is the information board, which serves as a visual medium for communicating essential messages to visitors. At Marisa Beach, existing information boards are limited, largely monolingual, and not systematically designed to meet diverse visitor needs. This study aims to develop bilingual information boards to support recreational tourism at Marisa Beach. A Research and Development (R&D) approach was employed using the Borg and Gall model, encompassing needs analysis, product planning, prototype development, expert validation, revision, and field testing. The resulting product consists of bilingual information boards in Indonesian and English containing site regulations, safety information, directional guidance, and brief descriptions of the destination. Expert validation results indicate that the product is appropriate for use after minor revisions, while field testing shows that the boards are readable, easy to understand, and positively received by visitors. These findings indicate that bilingual information boards enhance information accessibility and contribute to a more inclusive and well-organized recreational tourism environment. Consequently, the development of bilingual information boards is essential for improving tourism information services and supporting sustainable destination management at Marisa Beach.